BADIIY TARJIMANING OʻZIGA XOS XUSUSIYATLARI (Journal of Universal Science Research, 2025)
This article discusses the fact that literary communication is one of the most necessary factors for the development of any literature, how laborious the art of translation is in translating samples of Uzbek literature into English, and how poetic works differ from prose works in the same way and to the same extent. The existence of primary rules for a translator in translation, translation is a type of literary art, and translation is a science. In this sense, if a translator, as an artist of words, knows another language perfectly, but does not know his own language well, the work will be very strange and dull. The work of a translator and the relevance of literary translation today are discussed.